Comparison of goal-scoring patterns between the Euro and Copa América 2024 tournaments through a notational analysis - Ugalde-Ramírez, J. A.; Vasquez-Bonilla, A. (Scientific Journal of Sport and Performance, 2025)
This study aimed to analyse the goal-scoring patterns in the Euro and Copa America 2024 tournaments through notational methods. A total of 187 goals scored (117 in the Euro and 70 in the Copa America) were analysed. The goal-scoring categories include type of play, type of attack, interval time, starting zone of attack, finishing zone, previous action for scoring, and scoring technique. The results indicated that more goals came from organized attacks and throw-ins in the Euro, while free kicks were more effective in the Copa America. Quick attacks predominated in both tournaments; in Euro, most goals were scored between 16-30 minutes, and in Copa America, between 46-60 and 76-90 minutes. More goals originated from the own half, the right and central zones of the opponent's half in both tournaments, and they were finished in the central zone inside the penalty area, predominantly by shots. Semi-finalist teams in both tournaments scored more goals from deep passes and crosses. In the Copa America, attacks often start from the right zone of the opponent's half. In conclusion, similarities and differences in goal-scoring patterns were observed between the two tournaments. It is necessary to continue exploring associations between the sport performance and goal-scoring patterns.